Analisis Implementasi Pendidikan Karakter Berbasis Nilai Religius di Madrasah Ibtidaiyah Sunan Pandanaran Yogyakarta - Anggun Putri Melati; Muh Wasith Achadi (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2025)
This study analyzes the implementation of character education based on religious values at Madrasah Ibtidaiyah Sunan Pandanaran (MISPA) Yogyakarta, where character formation is cultivated as a living school culture. Grounded in pesantren tradition, MISPA integrates religious practices such as DDAH (prayer, dhuha, and Asmaul Husna), daily Qur’an memorization, congregational prayers, and thematic initiatives including the Anti-Bullying Declaration as structured habituation strategies that shape students’ everyday behavior. This research employed a descriptive qualitative approach, with data collected through observation, in-depth interviews, and documentation. Data analysis followed the interactive model of Miles and Huberman, encompassing data reduction, data display, and conclusion drawing and verification. The findings indicate that character education at MISPA is collaboratively planned, consistently implemented by teachers as role models, and continuously evaluated through behavioral observation and reflective practices. Character education emphasizes not only moral knowledge but also habitual action and the cultivation of religious awareness, aligning with the theoretical perspectives of Lickona, Bronfenbrenner, and Al-Ghazali. Despite challenges such as teachers’ workload, diverse levels of students’ awareness, and the influence of digital media, MISPA has successfully developed an educational ecosystem that fosters religiosity, discipline, and integrity